ON EARTH AS IN HEAVEN : An Exegetical and Theological Study of Psalm 73 - Nadupadavil, Theresa (Asian Horizons, 2011)
Psalm 73 occupies a very important place among the 150 psalms in the Psalter due to its profound theological insights and artistic greatness. It summarises the theological message of the Psalter, which is called a mini Bible, and is even entitled as the microcosm of the Old Testament. The beauty of this prayer along with its theological and canonical importance is evaluated, admired and expressed in many commentaries, books and articles. This recognition is reinforced in some monographs, yet, the theological consideration is not their focus. Hence, the overall purpose of the present study is threefold: 1) to present a systematic analysis of Ps 73’s place in the Canonical Psalter and to trace its literary background; including its genre, Sitz im Leben, structure, date, and authorship; 2) to make a close reading of the psalm which really suffer with text critical problems for its interpretation; and 3) to give a fresh theological understanding of the text and to examine its relevance in today’s context. To accomplish the aim of our study, a diachronic and synchronic reading of the text is presumable.